Systematic literature review: Determinants and contribution of restaurant tax to local own-source revenue in Indonesia - Karyanto, Karyanto; Sofyani, Hafiez (Journal of Accounting and Investment, 2025)
Research aims: This research aims to explore previous research related to the contribution of restaurant taxes in Indonesia to Local Own-Source Revenue (LOSR) and analyze studies from several angles.Design/Methodology/Approach: This research used a Systematic Literature Review, which consisted of three stages, namely the collection stage, by entering the search keywords "Contribution," "Restaurant Tax," and "Local Own-Source Revenue" in Google Scholar and Scopus from 2014 to 2023. Articles included in the research were assessed based on their ranking in the SINTA and Scopus indexes. The presentation stage focused on the research background, methods, and findings. After applying a series of criteria, 44 articles were obtained.Research findings: Restaurant tax research in Indonesia has been active since 2014, mostly in SINTA 4, in Java and using quantitative methods. Restaurant tax has not provided optimal contribution to Local Own-Source Revenue due to lack of compliance and awareness of taxpayers.Theoretical contribution/Originality: More generally looking at the contribution of restaurant taxes in Indonesia, and systematic literature review research published in the indexed journals Sinta and Scopus has never been found and carried out. Practitioner/Policy implication: Provide considerations to the Regional Government to pay attention to LOSR achievement factors, especially restaurant tax.Research limitation/Implication: This research only focuses on restaurant taxes in Indonesia.